The USE OF DRONES FOR MONITORING POLICE ACTION IN SOCIAL CONFLICTS: A REVIEW OF THE LITERATURE IN THE LAST 5 YEARS - Reyes Valdivia, Carlos Alberto (2022)
Social conflicts lead to negative effects against the well-being of the citizen or a society. By way of reducing this fact, technology is frequently an ally that allows counteracting these altercations induced or not by an organized human group. The use of drones would allow, in this sense, to guarantee citizen security and coexistence in the face of possible social conflicts. This research under a qualitative approach using a systematic review of the literature of the last five years, with the general objective through the review to determine if the use of the drone violates Human Rights in the monitoring of police actions against Social Conflicts. , in the period 2017 to 2022, within the Scholar Google and Redib databases. As part of the results, an increase in the publication of indexed articles is observed in the years 2017 to 2021. In addition, within the linked articles, articles whose approach or theme is associated with the technical, warlike field are considered as exclusion criteria. , sports, entertainment, military. In conclusion, it is determined that the use of the drone in police actions in general does not harm human rights, this tool protects the Human Rights of all participants in all types of scenarios, especially in social conflicts; Likewise, it is necessary to develop a manual or protocol to minimize cases of social violence, continuing with studies, which contemplate aspects not foreseen in the current regulations regarding the drone.